(untitled) (Hungarian Journal of Industry and Chemistry, 2010)
The mobility of the globalized world is supported by internal-combustion engines, which generally use fossil fuels. City people have to move daily from place A to B. For that reason cities have public transport systems, including local bus as an important element. As the bulk of the population is concentrated in the city, the atmospherical emissions of local buses have a considerable impact on human health. This study analyses these impacts using the methodology of LCA and the database of the ARTEMIS project. The whole study includes the emissions models of pre-euro and euro 1-5 buses, CNG, biodiesel and hydrogen buses, and the fuel production. Furtermore seven scenarios for modeling traffic situations are included, too. For the impact assessment three CML2001 indicators are used. Global warming potential (GWP) is for assessing the global impacts, carbon footprint; human toxicity potencial (HTP) and photochemical ozone creation potential (POCP) are used for the estimation of impacts in urban environments.